Reproducing knowledge in construction expertise: a reflexive theory, critical approach. Issue 7 (2nd August 2016) - Kanjanabootra, Sittimont; Corbitt, Brian
Abstract : An auto-ethnography and then analyses of narratives and ethnographies of other construction professionals are used to argue that reproduction of knowledge and expertise development is constrained by both normative professional thinking and a discourse of economic constraint generated by a highly competitive marketplace with a focus on time, cost, and quality trade-offs. The analysis of construction professionals' narratives suggests that expertise development in construction is essentially an incremental process built on scenarios and influenced mostly by context and people, discourses of practices, legalities and professional expectations. Sometimes that incrementalism is distorted through radical innovation, but that is rare. Construction expertise in these stories is reproduced from base level learning and grows through practice. Practitioners, it is argued, accumulate knowledge and expertise, but the practice that emanates remains bounded within prevailing discourse which itself changes incrementally.